2018
DOI: 10.1177/1098300718768217
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Evidence-Base of School-Wide Positive Behavior Interventions and Supports Through Two Quality Appraisal Processes

Abstract: One ongoing challenge within education is preventing and responding effectively to problem behavior. In fact, research over the past two decades has focused on developing comprehensive approaches to prevent problem behavior and intervene at the first signs of student risk to reduce the likelihood of chronic and more intense problem behavior patterns (Horner, Sugai, & Anderson, 2010). Positive Behavioral Interventions and Supports (PBIS) is a framework for organizing academic, behavioral, and social-emotional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 27 publications
(73 reference statements)
2
26
0
1
Order By: Relevance
“…We found a statistically significant effect size for all behavior outcomes and that there was no difference in the overall effect size for suspensions, ODR, or other behavioral outcomes. As noted, the Mitchell et al () did not calculate effect sizes, but found generally positive results, which is aligned with our findings here. No prior systematic review or meta‐analysis reviewed the effect of SWPBIS on academic achievement.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We found a statistically significant effect size for all behavior outcomes and that there was no difference in the overall effect size for suspensions, ODR, or other behavioral outcomes. As noted, the Mitchell et al () did not calculate effect sizes, but found generally positive results, which is aligned with our findings here. No prior systematic review or meta‐analysis reviewed the effect of SWPBIS on academic achievement.…”
Section: Discussionsupporting
confidence: 93%
“…The current review synthesizes the growing evidence of SWPBIS effects on behavioral, academic, and organizational outcomes and extends prior reviews Mitchell et al, 2018;Solomon et al, 2012) by including unpublished studies and employing a RVE meta-analysis. Overall, we found statistically and educationally significant effects of SWPBIS on all three school-level domains.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations